Global Jihadist Terrorism Terrorist Groups, Zones of Armed Conflict and National Counter-Terrorism Strategies - Burke, Paul; Elnakhala, Doaa'; Miller, Seumas (Edward Elgar Publishing, 2021)
This insightful book provides a unified repository of information on jihadist terrorism. Offering an integrated treatment of terrorist groups, zones of armed conflict and counter-terrorism responses from liberal democratic states, it presents fresh empirical perspectives on the origins and progression of conflict, and contemporary global measures to combat terrorist activity.